Analisis Volume untuk Perbandingan Minat Investor Disekitar Ex-Dividend Date pada Emiten Kategori LQ-45 Tahun 2017 - Istahargyo, Byantoro; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
There are two approaches that describe investor desires, namely Bird in The Hand and Tax Preference. This study aims to see what approaches tend to be more interested by Indonesian investors. This research was conducted on the volume of shares of companies listed in the LQ-45 index listed on the Indonesia Stock Exchange (IDX) in 2017. The companies that were sampled were selected using purposive sampling method to obtain a sample of 46 companies. Stock trading volume is measured by Trading Volume Activity (TVA). The analysis technique used in this study is descriptive statistical test, normality test, paired sample t test and wilcoxon sign rank test. Test results can be concluded that there is a significant difference between stock trading volume before and after the ex-dividendd date. This shows that the ex-dividend date event affected the activity of stock trading volume and responded by investors. Keywords: TVA, Volume of Stock Trading, Ex-Dividend Date.